2014
DOI: 10.3109/00016489.2013.868602
|View full text |Cite
|
Sign up to set email alerts
|

Delayed facial nerve palsy after surgery for the Esteem®fully implantable middle ear hearing device

Abstract: None of the patients presented with a FN deficit in the first postoperative days. In three patients (8.8%), FN palsy developed after 7 days (two patients) and 10 days (one patient), and the severities were HB 4 (two cases) and HB 5 (one case). All patients fully recovered (HB 1) after 6-8 weeks. In 10 of the 34 implanted subjects (29.4%), taste disturbances were found on postoperative day 1, and these impairments remained in only 6 (17.6%) patients at the 3-month postoperative follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…Barbara et al reported a rate of 8.8% delayed facial nerve paresis in 38 subjects, with all achieving full recovery and no permanent paresis. 17 Two reports of facial nerve paralysis in large numbers of cochlear implant cases found rates of 1.1% and 0.62% temporary paralysis, with incomplete recovery rates of 0.1% and 0.15%. 18,19 The slightly higher incidence of facial nerve dysfunction with this totally implantable AMEI may be partially attributable to the very extensive facial recess exposure required in this implant surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barbara et al reported a rate of 8.8% delayed facial nerve paresis in 38 subjects, with all achieving full recovery and no permanent paresis. 17 Two reports of facial nerve paralysis in large numbers of cochlear implant cases found rates of 1.1% and 0.62% temporary paralysis, with incomplete recovery rates of 0.1% and 0.15%. 18,19 The slightly higher incidence of facial nerve dysfunction with this totally implantable AMEI may be partially attributable to the very extensive facial recess exposure required in this implant surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of 1.7% delayed‐onset facial nerve paralysis with full recovery and 0.6% immediate‐onset with incomplete recovery compare favorably to other centers using the same implant and are slightly higher than with cochlear implant surgery. Barbara et al reported a rate of 8.8% delayed facial nerve paresis in 38 subjects, with all achieving full recovery and no permanent paresis . Two reports of facial nerve paralysis in large numbers of cochlear implant cases found rates of 1.1% and 0.62% temporary paralysis, with incomplete recovery rates of 0.1% and 0.15% .…”
Section: Discussionmentioning
confidence: 99%
“…Among the true complications, the need for explantation occurred in six subjects: for skin dehiscence (one subject), loud noise (one subject), tinnitus (one subject), and hearing threshold deterioration (three subjects). Four subjects required a surgical revision and in about 9% of the cases, a delayed transient facial palsy was observed, with remarks that were object of a previous publication [8].…”
Section: Complicationsmentioning
confidence: 88%
“…Although other authors have reported delayed facial nerve palsy with these implants, none were seen in our series. 19 Six cases (4.9 per cent) were aborted because of limited anatomic space or inadequate ossicular vibration. Pre-operative highresolution CT of the temporal bone must be obtained prior to surgery to ensure adequate space for the implant.…”
Section: Discussionmentioning
confidence: 99%